Réponses

2012-12-29T00:07:19+01:00

-12(-5+3z) =  (-12) × (-5) + (-12) × 3z = 60 -36z

 

(3z+4)(5-6z) = 3z × 5 -6z × 3z + 4 × 5 -6z × 4 = 15z -18z² + 20 -24z = -18z²-9z+20

2012-12-29T00:32:06+01:00

Coucou,

 

1)-12(-5+3Z)

il s'agit ici, de a (b + cz) = (a x b) + (az x c )

 

Donc (-12) × (-5) + [(-12) × 3z] = 60 -36z

 

Et (3z+4)(5-6z), c'est du type : 

(az + b) (c - dz) = (az x c) - (az  x dz) + (b x c) -(b x dz) 

 

Donc (3z+4)(5-6z)

= (3z × 5) - (6z × 3z) + (4 × 5)  -(6z × 4)

= 15z -18z² + 20 -24z

-18z² + 15z-24z+ 20 on le met en ordre

= -18z²-9z+20 on finalement additionne les z

 

j'espère que tu as compris

 

voilà ,)